PD Localization - Norasage Pattanadech; Rainer Haller; Stefan Kornhuber; Michael Muhr (My University, 2023)
Partial discharge (PD) measurement is very important for evaluating the integrity of the electrical insulation system. PD localization can be divided into different ways according to the criteria used. In this chapter, the PD localization is classified into two groups, i.e. the PD localization for internal insulation and the PD localization for external insulation. PD localization techniques generally applied for the internal insulation – i.e. pulse time arrival method, auscultatory method, triangulation method, and bouncing particle localization method – are described. For external insulation, the PD localization can be achieved by using a corona camera or an airborne acoustic probe. The optical PD measurement utilizing the corona camera or the acoustic PD measurement employing the airborne acoustic sensor is superior to the conventional electrical PD measurement. This is because applying the coronal camera or the airborne acoustic sensor for corona discharge and surface discharge detection needs simple procedures to locate the PD source.
Keywords: High voltage insulation and dielectric phenomena; Advanced Fiber Optic Sensors; Water Systems and Optimization